Alterations of DNA damage response genes correlate with response and overall survival in anti‐PD‐1/PD‐L1‐treated advanced urothelial cancer. (23rd October 2020) - Joshi, Monika; Grivas, Petros; Mortazavi, Amir; Monk, Paul; Clinton, Steven K.; Sue‐Ann Woo, Michele; Holder, Sheldon L.; Drabick, Joseph J.; Yin, Ming
Abstract: DNA damage response (DDR) gene alterations in cancer are associated with a higher tumor mutational burden (TMB) and may impact clinical outcomes of urothelial cancer (UC). Here, we explore the prognostic role of DDR alterations in advanced UC treated with anti‐PD‐1/PD‐L1 agents. The study included 53 patients who had FoundationOne genomic sequencing and received anti‐PD‐1/PD‐L1 therapy. Fisher exact test and trend test were used to assess differences in objective response rate (ORR). Overall survival (OS) was measured from the time of initial UC diagnosis and Cox proportional hazard regression analysis was performed to calculate hazard ratio (HR) and 95% confidence interval (CI). The cohort had a median age of 66 with 64% receiving platinum‐based chemotherapy. DDR alterations (including ATM ) were associated with a non‐significantly higher ORR to PD‐1/PD‐L1 blockade (41% vs. 21%, p  = 0.136). Patients with DDR alterations (excluding ATM) had non‐significantly longer OS, likely due to a small sample size (HR = 0.53, 95% CI 0.20–1.38, p  = 0.19). ATM alterations were associated with a non‐significantly higher ORR (40% vs. 29%, p  = 0.6), but also with significantly shorter OS (HR = 5.7, 95% CI 1.65–19.74, p  = 0.006). Patients with ≥ 3 DDR alterations (including ATM ) had substantially higher TMB ( p  = 0.01) and higher ORR (80%) with PD‐1/PD‐L1 blockade versus 24% ORR in patients with <3 DDR alterations. In summary, DDR alterations were associated with non‐significantly higher ORR and longer OS for patients with advanced UC receiving anti‐PD‐1/PD‐L1 agents. ATM alterations were associated with shorter OS. Abstract : DDR alterations are associated with higher ORR and nonsignificantly prolonged OS in patients with advanced UC receiving PD‐1/PD‐L1 inhibitors. However, presence of ATM alterations correlated with shorter OS, irrespective of a nonsignificant trend towards higher ORR to anti‐PD‐1/PD‐L1 agents.